(untitled) (Fiep Bulletin - online, 2015)
The objective of this article is to identify and to understand the directions of adventure and the leisure that the practical one of the vaquejada one assumes in the speeches of the practitioners, Expresses through a half-structuralized interview and the projetiva technique of associations of ideas to the inductive words - vaquejada; horse; challenge; mat; ox; courage; adventure; oxwas valid; risk; leisure; track; zero ox; fear; vaquero that they had been evaluated through the speech analysis. The carried through study it showed the existence of the diverse faces of the vaquejada one and its practitioners who we foresaw in our hypotheses - between them the adventure and the leisure.